Pengaruh Jenis Edukasi Terhadap Performansi Pengemudi dengan Karakter Risk Taker - Dian Tiara Rezalti (Faculty of Engineering, Universitas Gadjah Mada, 2016)
The Government has made traffic laws and regulations to create a motor vehicle safety and in order to reduce the number of fatal and serious injuries that occur in motor vehicle crashes every year. However, it’s not much effecting to diminish numbers of road accident causing by lack of knowledge, insights, driving experience, and often to take a risk. This study aimed to identify the effective education in safety driving to improve the driver’s performance which has a risk taker characteristic. This study was conducted in a laboratory simulation of ergonomics with the respondent amounted 30 people aged 18-25 years and classified into three groups: 10 respondents are educated by using a module, 10 respondents are educated by watching a video, and 10 respondents directly practice using a simulator. Holt & Laury’s Questionnaire is used to knowing Risk Attitude of respondents. This study showed that video education is the most effective education to reduce a numbers of driving perform interference for those man and woman’s respondents and afterwards followed by module’s education and the last intended by without educationKeywords: risk taker, impaired driving performance, performance time on a task